(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Describe the experience of patients receiving inpatient treatment at Ha Tinh Rehabilitation Hospital in 2023 and analyze some related factors. Method: Cross-sectional descriptive study conducted on 238 inpatients at Ha Tinh Rehabilitation Hospital from May 2023 to July 2024. The study used the available Vietnamese version of the CAHPS toolkit in the form of interviews. Results: The overall positive patient experience was 79.61%. The proportion of patients with positive experiences is high in the following aspects: when hospitalized (92.7%), nurse’s care (82.1%), doctor’s care (91.7%), machinery and tools (94.3%), when completing hospital discharge payment procedures (95.5%), and upon discharge from the hospital (96.3%). Factors related to the experience of patients receiving inpatient treatment are that patients with health insurance cards have 3.66 times more positive experiences than the group without health insurance cards, Patients treated for the second time experienced 2.99 times more positive experiences than the group treated for the first time, patients discharged from the hospital in a better condition had 4 times more positive experiences than the go home/transfer group. Conclusions: Positive experience of inpatients at the Ha Tinh Rehabilitation Hospital reached 79.61%. It is necessary to train on communication and behavior, improve morale and attitude to serve patients and strengthen patient room hygiene.